INTERFERENSI BAHASA INDONESIA DALAM PEMAKAIAN BAHASA INGGRIS PADA WACANA TULIS SISWA - Lilik Uzlifatul Jannah (EDU-KATA, 2018)
The purpose of this study were (1) Describe the factors that background Indonesian interference in the use of English writing discourse of SMPN I Tikung student, (2) Describe the factors that background Indonesian interference in the use of English language written discourse SMPN I Tikung, (3) Describe the effect of Indonesian interference in the use of English writing discourse students of SMPN I Tikung, and (4) Describe efforts to address the events of Indonesian interference in the use of English language written discourse students of SMPN I Tikung.The research method used is descriptive qualitative research. Data captured through student discourse test and interview students and teachers. Source of data used in discourse writing in English is the student, and interviews are students and teachers of SMPN 1 Tikung at the time of the learning process. Collection techniques using student language identification sheet instruments. while the collection technique using interview questions instrument sheet students and teachers.Based on the results of the study, (1) interference caused by two factors: linguistic and non-linguistic factors. (2) forms of interference syntactic occur include, the use of a noun phrase consists usage noun phrase followed by a noun, and a noun followed by an adjective, the use of possessive pronouns, use the relationship numeralia, the use of adjectives, the use of adverbs of time, the use of information pointing place, the use of adverbs, the use of conjunctions expressing the relation of meaning way, the use of adverbs that indicate quality, and the use of the phrase, (3) the effect of Indonesian interference into English discourse writing students is due to the use of a relatively dominant Indonesian English language learning. and (4) the effort which is taken to avoid interference Indonesian into English discourse writing students the cooperation and efforts to earn good students, teachers, and schools in the form of intra-curricular and extracurricular.